1984
DOI: 10.1111/j.1398-9995.1984.tb01964.x
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for Specific Immunotherapy of Grass Pollen Allergy with Extracts of Rye Pollen

Abstract: In immunotherapy of grass pollen allergy, an extract of rye (Secale cereale) is often included. The aim of this study was to investigate by skin prick test (SPT) and immunochemical methods whether rye pollen contains specific allergens justifying the use of this extract separately. Twenty grass pollen allergic patients were skin prick tested with a dialysed freeze-dried raw extract of rye pollen (Sc), timothy extract (Soluprick SQ, 1 HEP) and two other rye extracts (Soluprick). Sera from the patients were RAST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Comparing the results obtained in this study to those achieved by CRIE [21,28] using the same amount of allergen, Immunoprint proves to be better in terms of time needed (1 day versus several days) and numbers of allergens recognized (more than 30 versus 16). Furthermore, there is no need to use radiolabeled second antibodies [36].…”
Section: Discussionmentioning
confidence: 79%
“…Comparing the results obtained in this study to those achieved by CRIE [21,28] using the same amount of allergen, Immunoprint proves to be better in terms of time needed (1 day versus several days) and numbers of allergens recognized (more than 30 versus 16). Furthermore, there is no need to use radiolabeled second antibodies [36].…”
Section: Discussionmentioning
confidence: 79%
“…The immunochemical divergence of group V and group I allergens has been hidden by the fact that the heavily radiostained group V precipitates usually are overlaying the rather badly defined group I precipitates. However, after reevaluation of elder CRIE investigations from our laboratory, the group I component is recognized as the group V 'shadow' in the precipitation patterns, for example Agl3 in an early investigation on Secale cereale [27].…”
Section: Group V Allergensmentioning
confidence: 99%
“…This study also suggested that exposure to large amounts of S. cereale pollen, in patients living near rye cultivation areas, for example, does not result in a significantly higher rate of sensitization to S. cereale allergens when compared to D. glomerata (orchard grass) allergens. Skin prick tests performed in patients with a clear history of allergic rhinitis during the grass pollen season revealed that all patients were reactive to extracts made from either S. cereale pollen, or from pollens from L. perenne , P. pratensis , P. pratense , D. glomerata and A. odoratum [1, 7, 8].…”
Section: Molecular Immunologymentioning
confidence: 99%
“…Allergy to rye ( Secale cereale) pollen is frequent in northern Europe where this cereal is widely cultivated [1]. Rye is the only true wind‐pollinated cereal commonly grown in Europe and should not be confused with rye grass ( Lolium perenne ).…”
Section: Introductionmentioning
confidence: 99%